Pendampingan Usaha Bukik Nabu (UBUNA) dalam Budidaya Lebah Tanpa Sengat (Galo-Galo) dan Pengembangan Produk Turunannya di Limau Manis, Padang - Henny Herwina; Eli Ratni; Wellyalina Wellyalina; Jasmi Jasmi; Virtuous Setyaka (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2021)
Galo-galo is a stingless bee that has been cultivated for the last ten years because of its potential as a producer of very good quality of honey. In addition, galo-galo is also capable of producing bee pollen and propolis, which are used to healthy and cosmetics products. The stingless bee keeping, also known as meliponiculture, is a sustainable activity that does not harm the environment, moreover it helps to increase productivity of several crops. This community service activity was carried out to accompany Bukik Nabu (UBUNA) business partners to develop the meliponicuture in residential area in Limau Manis Padang. The program included as assisting partners in developing several processed products based on honey, bee pollen and propolis. The method used was direct mentoring which begins with discussions and providing a Focus Group Discussion (FGD) with partners, residents and local government. Several agreements and work plans have been made, i.e. enrichment of knowledge in galo-galo cultivation techniques and continuous propagation of feed plants for the bees’ production, furthermore assisting in produce of the food products, improving the packaging and marketing system of downtream products from meliponiculture.